Cognition in HCI: An Ongoing Story - Hurtienne, Jörn (Human Technology, 2009)
The field of human computer interaction (HCI) is deeply rooted in cognitive science. But can cognitive science still contribute to the newest developments? This article introduces the recent trends towards "embodied cognition." Then research on image schemas and their metaphorical extensions is reviewed as an example of how understanding a special branch of embodied cognition can be useful to HCI. Special emphasis is placed on the validity of the theory and its practicability in different phases of the user interface design cycle. It is concluded that cognition can still contribute to current HCI and that the dialogue between the different schools of thought is beneficial to the field.